2012
DOI: 10.1016/j.pneurobio.2012.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the age-related decline on spatial learning and memory tasks in rodent models: N-methyl-D-aspartate receptors and voltage-dependent Ca2+ channels in senescent synaptic plasticity

Abstract: In humans, heterogeneity in the decline of hippocampal-dependent episodic memory is observed during aging. Rodents have been employed as models of age-related cognitive decline and the spatial water maze has been used to show variability in the emergence and extent of impaired hippocampal-dependent memory. Impairment in the consolidation of intermediate-term memory for rapidly acquired and flexible spatial information emerges early, in middle-age. As aging proceeds, deficits may broaden to include impaired inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
159
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 147 publications
(170 citation statements)
references
References 360 publications
(593 reference statements)
9
159
2
Order By: Relevance
“…A positive correlation between V T and age was observed and so future studies, especially if involving poorly matched subgroups, should model this as a covariate in the analyses. This finding appears at odds with the agerelated declines in cerebral blood flow (39) and NMDA receptor function (40). However, it is possible that the relationship between 18 F-GE-179 V T and age is nonlinear.…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation between V T and age was observed and so future studies, especially if involving poorly matched subgroups, should model this as a covariate in the analyses. This finding appears at odds with the agerelated declines in cerebral blood flow (39) and NMDA receptor function (40). However, it is possible that the relationship between 18 F-GE-179 V T and age is nonlinear.…”
Section: Discussionmentioning
confidence: 99%
“…Next we consider the possibility that reduced levels of neuromodulators in slices from aged rats limited the induction NMDAR-LTD. In CA1 and cortical synapses Gq-coupled receptors promote NMDAR-LTD (Choi et al, 2005;Huang et al, 2012), and this type of modulation is an attractive candidate substrate for the behavioral gating of LTD observed in vivo (Hagena and Manahan-Vaughan, 2011). We found that stimulation of ␣1 adrenergic receptors (coupled to Gq) with bath application of methoxamine (5 M during LFS), a manipulation that rescues the loss of NMDAR-LTD in the visual cortex after dark rearing (Guo et al, 2012), did not improve NMDAR-LTD in slices from AU rats (96.50 Ϯ 1.68% of LTD, n ϭ 6 slices, 2 rats; data not shown).…”
Section: Aging Reduces Nmdar-ltd In Both Aged Groups and Mglur-ltd Inmentioning
confidence: 99%
“…However, the central premise-that the NR2b subunit promotes LTD over LTP-has been challenged by several studies reporting that NR2b-containing receptors are not essential for LTD (Morishita et al, 2007), but rather promote LTP over LTD (Philpot et al, 2003;Barria and Malinow, 2005). Another possibility has invoked an age-dependent change in intracellular Ca 2ϩ homeostasis as a basis for reduced LTP and enhanced LTD, which is observed in the SC3 CA1 pathway of some rat models of aging (Burke and Barnes, 2006;Oh et al, 2010;Foster, 2012). Note, however, that both altered NMDAR subunit composition and altered Ca 2ϩ homeostasis would predict that NMDAR-LTP should also be affected.…”
Section: Mechanisms Of Altered Plasticity In the Aged A/c3 Ca3mentioning
confidence: 99%
See 2 more Smart Citations